Development of Teacher Beliefs through Online Instruction: A One-Year Study of Middle School Science and Mathematics Teachers’ Beliefs About Teaching and Learning - Sissy S. Wong (Journal of Education in Science, Environment and Health)
Understanding teachers’ beliefs is important because beliefs influence teacher decisions.  In science, teacher beliefs impacts how science curriculum is interpreted and implemented in the classroom. With the push for STEM education in the United States, it is also critical to examine teacher beliefs of those that integrate science in the classroom. This study of N=21 middle school science and mathematics teachers’ beliefs in the United States found one year of a graduate online program that emphasized inquiry-based instruction and student-centered frames-of-mind influenced participants’ beliefs. Overall, all participants veered toward more student-centered beliefs. When types of beliefs were disaggregated, participants’ beliefs about teaching and beliefs about learning both veered towards more student-centered position. It was also found that teachers’ beliefs significantly changed regardless of years of experience. One surprising find was science teachers’ beliefs changed significantly while mathematics teachers’ beliefs did not. Findings from this study support the notion that formal knowledge impacts teacher beliefs.